List of IMF Member Countries with Delays in Completion of Article IV Consultations or Mandatory Financial Stability Assessments over 18 Months. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
The following table lists the IMF members for which the Article IV consultation or the mandatory financial stability assessment has been delayed by more than 18 months. The delay is counted past the scheduled expected date, plus any applicable grace period.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Consultation; Fund Staff; IMF Member Countries With Delay; List Of IMF Member Country; PP; Argentina